Decoding Digital Identities and Exploration of Whatsapp Status Content and Lecturers’ Perceptions of Uganda Christian University- Bishop Barham University College Kabale Students’ Academic and Social Identity - Ivone Arinda (Uganda Christian University, 2025)
Lecturers’ perceptions of students are based purely on academic performance, classroom engagement and professionalism. Social media would serve only as a supplementary communication tool without affecting academic relationships or perceptions. WhatsApp statuses often display content ranging from academic achievements to casual or controversial opinions. These updates can subconsciously influence lecturer’s perceptions, sometimes leading to biases about students’ academic abilities and social identities. Existing studies often overlook the specific cultural and institutional contexts, and there is a need for more robust methodologies to capture the complexity to these perceptions and their potential biases. Furthermore, the long-term effects of these perceptions on student-lecturer relationships and academic outcomes remain largely unexplored